The Non-Categorical Imperative: Martin Buber's Line of Demarcation and the Doctrine of the Descent of the Tzaddik in Hasidism - Hadad, Yemima (Jewish studies quarterly, 2024)
Buber's concept of the »line of demarcation« has been criticized by a number of thinkers from the perspectives of philosophy and Kantian ethics. Ernst Simon, who wrote an extended essay on the topic, called it a »non-categorical« principle, while Hugo Bergman and Steven Schwarzschild explained it through Buber's dialogical philosophy, highlighting its failure to articulate clear ethical imperatives. Today Buber's line of demarcation is hardly noticeable in the scholarly literature, mainly because it seems to offer little practical value and concrete guidelines. Yet, as this essay argues, Buber's situational ethics and his line of demarcation were shaped by profound theological doctrines. It shows that the line of demarcation was inspired by the doctrine of the descent of the tzaddik in Hasidism and the doctrine of »descent for the sake of ascent« (yeridah letzorech aliyah). These doctrines allow us to view Buber's ethical vision again as a »non-categorical imperative,« which aligned with his political-theopolitical approach and his life-long engagement with hasidic thought.